POTENSI PENGEMBANGAN EKOWISATA DI NAGARI KOTOBARU, KECAMATAN X KOTO, KABUPATEN TANAH DATAR, SUMATERA BARAT - Firdaus Firdaus; Rio Tutri (Jurnal Kawistara, 2017)
In recent years, tourism has been the important economic and social activities in the world. Tourism studies that showed the impacts of tourism activity to economic countries were significant. In Indonesia, the developing of tourism conducted as primary sector to support the other economic sectors, in particularly in both trade and service. The Indonesian tourism development primary is nature and culture. This research aimed to analyze and describe ecotourism potency of  Nagari Kotobaru, Kabupaten Tanah Datar as the door to summit of Merapi Mountain in West Sumatera. This research conducted with qualitative approach in 2016. Data was collected with observation, depth interview and document study. The potency ecotourism development was analyzed through SWOT analysis. The result showed that the Nagari Kotobaru strength was in poor and there were some weakness too. Although, Nagari Kotobaru have potencies to be created as an ecotourism area without serious threat. Based on the SWOT analysis, the mode of ecotourism that would be applied to Nagari Kotobari was ecotourism community type.